Understanding of Sharia-based Financial Accounting - Erwindiawan Erwindiawan; Liestyowati Liestyowati; Vina Budiarti Mustika Sari; Selva Temalagi; Hengky Leon (Enrichment : Journal of Management, 2022)
This study aims to explore various sources of information related to understanding Islamic sharia-based financial accounting. The author believes that quite a several studies have been carried out that discuss the issue of Islamic financial accounting. However, very few have discussed it to deepen and sharpen their understanding of Islamic accounting, considering that most of the Indonesian population is Muslim and currently carrying out Islamic law both conventionally and personally. To enrich this study, we conducted data searches on publications in the form of books and journal scientific articles, which we studied carefully, involving coding of data evaluation data and drawing conclusions that meet the elements of high validity. After a series of studies and discussions, we can conclude that understanding Islamic-based accounting is essential for Muslims. This is related to many economical options that offer each other benefits and conveniences today. However, Muslims do not only look at the benefits but also the economic system must follow life's guidelines, namely the Qur'an and hadith. Thus, these findings strengthen reading comprehension and complement further studies.